Comparative analysis of arterial spin labeling and dynamic susceptibility contrast perfusion imaging for quantitative perfusion measurements of brain tumors - Jiang, Jingjing (e-Century Publishing Corporation, 2014)
We comparatively analyzed the difference between three-dimensional arterial spin labeling (3D-ASL) and the conventional dynamic susceptibility contrast (DSC) perfusion imaging in the setting of assessing brain tumor perfusion in 28 patients with proved brain tumors. All patients were scheduled with standard MRI, 3D-ASL and DSC scannings on a GE DISCOVERY MR 750 system. Maximal relative tumor perfusion was obtained based on the region of interest (ROI) method. A close correlation between 3D-ASL and DSC perfusion imaging was noted as manifested by the absence of significant differences between ASL nTBF and DSC nTBF when normalized to M (mirror region) and GM (contralateral gray matter). However, ASL nTBF was found to be highly correlated with DSC nTBF and DSC nTBV when normalized to M, GM and WM (contralateral normal white matter). Together, our data support that 3D-ASL possesses the potential to be a noninvasive alternate for DSC-MRI in assessing brain tumor perfusion in the setting of treatment prognosis and metastasis, particularly for those patients with renal failure and patients required for collection of follow up information.